2020
DOI: 10.1093/ecco-jcc/jjaa200
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicrons-Simulating Sustained Drug Release in Mesenteric Lymphatics for the Treatment of Crohn’s-Like Colitis

Abstract: Background and aims Alteration of both structures and functions of mesenteric lymphatic vessels is a typical hallmark of Crohn’s disease. Dysfunctional lymphatics was observed both in patients with Crohn’s disease [CD] and experimental colitis, suggesting mesenteric lymphatics could be potential therapeutic targets. This study was aimed to develop a nano-delivery system which can enhance drug delivery in mesenteric lymphatic tissues [MLT] and evaluate the therapeutic effects in Crohn’s coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…These nanomaterials can be packaged into chylomicrons and show an increase in transport through enterocytes compared to free drug or uncoated nanomaterials. Yin et al used a lipid-coated nanoparticle formulation to deliver an immunomodulatory drug, Laquinimod (LAQ), to treat Crohn's disease, an autoimmune disease [90]. They used a mesoporous silica nanoparticles coated with α-α dilaurin to mimic TGs [90].…”
Section: Lipid-based Delivery Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…These nanomaterials can be packaged into chylomicrons and show an increase in transport through enterocytes compared to free drug or uncoated nanomaterials. Yin et al used a lipid-coated nanoparticle formulation to deliver an immunomodulatory drug, Laquinimod (LAQ), to treat Crohn's disease, an autoimmune disease [90]. They used a mesoporous silica nanoparticles coated with α-α dilaurin to mimic TGs [90].…”
Section: Lipid-based Delivery Systemsmentioning
confidence: 99%
“…Yin et al used a lipid-coated nanoparticle formulation to deliver an immunomodulatory drug, Laquinimod (LAQ), to treat Crohn's disease, an autoimmune disease [90]. They used a mesoporous silica nanoparticles coated with α-α dilaurin to mimic TGs [90]. They also added an acid resistant coating to protect the nanoparticles from gastric fluids that would otherwise lead to their degradation [90].…”
Section: Lipid-based Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that mesenteric lymphatics may be a promising potential target for CD treatment. Recently, we found that intestinal inflammation was significantly improved by the application of lymphatics-targeting drug release in the IL-10 -/- spontaneous experimental colitis, suggesting that mesenteric LVs are potential targets for CD treatment[ 80 ].…”
Section: Lymphaticsmentioning
confidence: 99%